Muscle-tendon unit morphology, architecture and stiffness in relation to strength and responses to strength training - Massey, G. (2017)
This thesis examined the change in skeletal muscle architecture with contractile force production, the relationship of architecture with muscle strength parameters and if muscle tendinous tissue stiffness determines in vivo explosive strength (i.e. rate of torque development, RTD). Muscle and tendinous tissue adaptations to contrasting strength training regimes, and the potential capacity of these tissues to adapt following chronic strength training were also explored. Quadriceps femoris fascicle length (FL) decreased, while the pennation angle (PA) increased in a curvi-linearly manner from rest to maximal voluntary contraction (MVC) torque. Consequently, effective physiological cross-sectional area (effPCSA) during MVC was 27% greater than at rest, although effPCSA measured at rest and during MVC had similar correlations to maximal strength. In the earliest phase of contraction, FL, but not PA, was negatively related (R2=0.187) to voluntary RTD. Neither FL nor PA was related to maximal isometric or dynamic strength. Muscle-tendon unit (MTU) and patellar tendon (PT) stiffness were unrelated to voluntary and evoked RTD. Relative PT stiffness was also unrelated to relative RTD, although relative MTU stiffness was related to voluntary RTD (25-55%MVT, R2=0.188) and evoked RTD (5-50%MVT, R2=0.194). MTU stiffness increased after sustained-contraction (SCT, +21%), though not explosive-contraction strength training (ECT). PT stiffness increased similarly after ECT (+20%) and SCT (+16%), yet neither induced tendon hypertrophy. SCT produced modest muscle (+8%) and aponeurosis (+7%) hypertrophy. Chronic strength trained (CST: >3 years) males had substantially greater muscle and aponeurosis size, but similar tendon size as untrained controls (UNT) and short-term (12 weeks) strength trained (STT) individuals. Between these groups, at the highest common force, MTU stiffness was indifferent, while PT stiffness was similarly greater in STT and CST than UNT. These results suggest FL and PA have little influence on muscle strength and tendon stiffness has no influence on RTD. Maximum strength negated any qualitative influence of MTU stiffness on in vivo RTD. Component MTU tissues (muscle-aponeurosis vs. external tendon) adapt differentially depending on the strength training regime. Specifically, free tendon appeared to adapt to high magnitude loading, while loading duration is also an important stimulus for the muscle-aponeurosis. However, chronic strength training was not concordant with greater higher force MTU stiffness, and does not further increase higher force PT stiffness beyond the adaptations that occur after 12 weeks of strength training. Finally, no evidence was found for tendon hypertrophy in response to strength training.